Treatment of postoperative non-union with internal fixation loosening of Garden IV femoral neck fracture with teriparatide in a young adult: A case report - Lai, Lili; Li, Yifan; Shen, Miaoda; Wang, Xuanwei; Zhong, Cheng; Xu, Sanzhong (Frontiers in Surgery, 2022)
Background: Postoperative nonunion of femoral neck fracture often needs secondary operation. We report a case of postoperative nonunion of femoral neck fracture treated with teriparatide. Case presentation: A young male patient with Garden IV femoral neck fracture who had no obvious signs of healing 3 months after percutaneous hollow nail fixation which the fracture line was enlarged and the hollow nail was withdrawn. Bone nonunion healed after 6 months continuous subcutaneous injection of 20 mg/day of teriparatide after the patient refused a secondary surgery. As far as we know, there are no relevant reports yet. Conclusions: Teriparatide is expected to treat young patients with a displaced femoral neck fracture who have difficulty in healing before nonunion and avoiding secondary surgery.